The Relationship Between Parental Role And Peer Social Support With Adolescent Alcohol Consumption Behavior - Muhammad Maula Rizka; Tinon Citraning Harisuci (Journal of Research in Social Science and Humanities, 2024)
The role of parents and social support of peers can potentially cause an adolescent to have a high tendency of alcohol consumption behavior that causes indifferent behavior to the environment, loss of interest in the surrounding environment, irritability or anger, and lack of concern for the scope or social. The purpose of this study was to examine the relationship between parental role and peer social support with adolescent alcohol consumption behavior. This study uses quantitative research methods. The sampling technique used was non probability sampling with purposive sampling method. The number of participants was 173 respondents. The results showed that the pearson correlation value was 0.932 with sig. = 0,000 (? 0,05). This means that there is a highly significant relationship between parental role and peer social support with alcohol consumption behavior. The implication of this study is that there needs to be an intervention on parental role and peer social support in adolescents so that the level of alcohol consumption becomes low.